Pemanfaatan pekarangan dengan budidaya sayuran untuk pemberdayaan keluarga miskin di Kabupaten Sidrap - Abd. Muis; Muhiddin Palennari; Hartati Hartati (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
A house garden is potential to be managed for thecultivation of vegetables for the fulfillment of nutrition and arelative reduction in the cost of living of poor families. Thecondition of the land and the limited knowledge and life skillsof the poor in the Maritengngae District, Sidrap Regency,became the main limiting factor for the use of the garden forcultivation. The Community Service-Learning and CommunityEmpowerment activity program (KKN = PPM) of UNMorganized program for target families to provide knowledgeand skills in the manufacture of organic fertilizers andcultivation of hydroponic systems. The goal was achieved byusing training methods, demonstration plots and mentoring.The activities that were realized included: a) increasedknowledge and skills of target residents in making organicfertilizer from household waste, and vegetable cultivation ofhydroponic systems; and b) fulfillment of the need for severaltypes of vegetables through utilization of the garden forcultivation. If this activity is sustainable and well developed,then the needs for the vegetable foodstuffs of the targetresidents will be fulfilled independently.